Categorisation of Road Construction Projects’ Cost Overruns Causes using Factor Analysis - Ahmad, Z. B.; Anigbogu, N.; Molwus, J. J. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Cost overrun is a major problem in the construction industry and a threat to the financial freedom of any country. Considering that Nigerian roads are constructed at very high cost, cost overruns could lead to significant reduction in the quality and number of projects that can be implemented. A vast number of cost overruns causes have been identified by various studies. However, the large number of possible causes makes managing and controlling them very challenging. This study, therefore, aims at categorising the causes in order to simplify their minimisation by identifying their latent constructs. Seventy-one (71) factors identified through literature review and ranked by questionnaire survey respondents. The survey involved 267 respondents (clients, contractors and consultants) that have worked on road construction projects. The collected data were analysed using exploratory factor analysis. Eight factors emerged from the 42 retained causes of cost overruns; contract related, economic and political, design and documentation, financial related, technical related, policy related, construction management related, and natural related causes. With this classification, it is easier to identify the group that has the most significant causes of cost overruns thus providing more information for better management.